The use of impression management tactics in structured interviews a function of question type? - Ellis, Aleksander P. J.; West, Bradley J.; Ryan, Ann Marie; DeShon, Richard P. (The American Psychological Association, 2002)
This study investigated impression management tactic use during structured interviews containing both experience-based and situational questions. Specifically, the authors examined whether applicants' use of impression management tactics depended on question type. Results from 119 structured interviews indicated that almost all of the applicants used some form of impression management. Significantly more assertive than defensive impression management tactics were used, and among assertive tactics, applicants tended to use self-promotion rather than ingratiation. However, different question types prompted the use of different impression management tactics. Ingratiation tactics were used significantly more when applicants answered situational questions, whereas self-promotion tactics were used significantly more when applicants answered experience-based questions. Furthermore, the use of self-promotion and ingratiation tactics was positively related to interviewer evaluations.